2021
DOI: 10.1007/s11433-021-1722-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical relaxation and thermal creep of high-entropy La30Ce30Ni10Al20Co10 bulk metallic glass

Abstract: Dynamic mechanical relaxation is a fundamental tool to understand the mechanical and physical properties of viscoelastic materials like glasses. Mechanical spectroscopy shows that the high-entropy bulk metallic glass (La 30 Ce 30 Ni 10 Al 20 Co 10 ) exhibits a distinct β-relaxation feature. In the present research, dynamic mechanical analysis and thermal creep were performed using this bulk metallic glass material at a temperature domain around the β relaxation. The components of total strain, including ideal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 84 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…This means that the satisfaction of the time-temperature-superposition (TTS) principle is expected in many metallic glass-forming systems. Further detailed studies on the dynamic relaxation processes in metallic glasses can be found in literature [38][39][40][41][42] .…”
Section: Resultsmentioning
confidence: 99%
“…This means that the satisfaction of the time-temperature-superposition (TTS) principle is expected in many metallic glass-forming systems. Further detailed studies on the dynamic relaxation processes in metallic glasses can be found in literature [38][39][40][41][42] .…”
Section: Resultsmentioning
confidence: 99%
“…Previous related report revealed that the precipitation of the special structures at 1-2 nm scales of medium-range order (MRO) can alter the free volume distribution, thereby promoting the nucleation of shear bands in bulk materials, causing them to branch, deflecting their propagation direction, impeding their rapid propagation, and eventually leading to a large overall plastic strain. Therefore, based on the results of TEM observation and the corresponding SAED pattern, it is proposed that such an improvement in plasticity may attribute to the precipitation of α-Fe(Co, Ni) like clusters in the 0.3 and 0.6 at.% Cu-added alloys [39]. Additionally, it can also be noted that the further increase in Cu content to 0.9 and 1.2% leads to a consequent decrease in the plastic strain in the present HE-BMGs.…”
Section: Discussionmentioning
confidence: 99%
“…图中点划线区域为经验公式 包围区域 ous alloys with the glass transition temperature [31][32][33][34] , dotted area in the figure is the area surrounded by empirical formula .…”
Section: 玻璃形成熔体在冷却过程中 其动态弛豫行为mentioning
confidence: 99%